Pengaruh pemberian air rebusan daun avokad dan melati terhadap tekanan darah pada lansia dengan hipertensi derajat 1 di Wilayah Kerja Puskesmas Tlanakan Kabupaten Pamekasan - Dina Novarita Kusuma Wardani; Lianita Primi Octaviana; Eka Deviany Widyawaty; Dessy Hidayati Fajrin (2022)
Hypertension is the silent killer disease because there are no signs or symptoms that can be seen from theoutside, which will cause complications in target organs. The purpose of this study was to analyze the effectof giving boiled water with avocado and jasmine leaves on blood pressure in the elderly with hypertensiongrade 1 in the Tlanakan Public Health Center, Pamekasan Regency. This research is quantitative researchwith a quasi-experimental method. The sample in this study was elderly with hypertension grade 1 who metthe inclusion criteria in the Work Area of ​​the Tlanakan Health Center, Pamekasan Regency as many as 42people. Statistical test using Paired Sample T-Test. The results showed that before being given theintervention of boiled water of avocado and jasmine leaves, most of the respondents were elderly withhypertension grade 1, namely 36 people (85%), after being given the intervention of boiled water of avocadoand jasmine leaves there was a significant decrease in blood pressure, most of the respondents 29 peoplebecame Pre Hypertension (69%). The results of the Paired t-test analysis show that the p-value is 0.000.From the results of the study, it can be concluded that there is an effect of giving boiled water of avocadoand jasmine leaves on blood pressure in the elderly with hypertension grade 1 in the Work Area of ​​theTlanakan Public Health Center, Pamekasan Regency. Suggestions for this research are that it is hoped thatthere will be further research on local resources for hypertension.